2014
DOI: 10.1007/s00454-014-9586-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Distances on Curves Via Rigidity

Abstract: Abstract. It is shown that N points on a real algebraic curve of degree n in R d always determine n,d N 1+ 1 4 distinct distances, unless the curve is a straight line or the closed geodesic of a flat torus. In the latter case, there are arrangements of N points which determine N distinct distances. The method may be applied to other quantities of interest to obtain analogous exponent gaps. An important step in the proof involves understanding the structural rigidity of certain frameworks on curves.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…In [4], Charalambides establishes a version of Theorem 1.1 with the weaker lower bound c d n 5/4 . He combines the technique of [6] with analytic as well as algebraic tools, and even extends it to higher dimensions, with a more complicated set of exceptions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In [4], Charalambides establishes a version of Theorem 1.1 with the weaker lower bound c d n 5/4 . He combines the technique of [6] with analytic as well as algebraic tools, and even extends it to higher dimensions, with a more complicated set of exceptions.…”
Section: Introductionmentioning
confidence: 97%
“…This makes it possible to extend their methods to parametrizable curves, but makes it harder to extend to general algebraic curves, which are defined by an implicit equation. In [4], this is overcome using the Implicit Function Theorem, which allows implicit curves to be "parametrized" analytically. One important new element of our proofs is that we construct the new curves in an implicit and algebraic way (see in particular (1) in Section 3), making parametrization unnecessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition on the curve is tight in the sense that for any excluded curve there is a bilinear form that can take a linear number of values on that curve. To the authors, it was surprising that such curves can have large degree, whereas previous evidence (namely [8] and [20]) suggested that the exceptional curves in such problems have degree at most three. The description of the exceptional curves in Theorem 3.3 is very succinct but requires some clarification.…”
Section: Other Polynomials On Curvesmentioning
confidence: 97%
“…Charalambides [8] also considered the function A(p, q) = p x q y − p y q x , which (in R 2 ) gives twice the signed area of the triangle spanned by p, q, and the origin. He proved that, for P contained in an irreducible algebraic curve C in R 2 , we have |A(P ×P )| = Ω d (|P | 5/4 ), unless C is a line, an ellipse centered at the origin, or a hyperbola centered at the origin.…”
Section: Other Polynomials On Curvesmentioning
confidence: 99%